Patterns and outcome of neonates with congenital anomalies in a neonatal intensive care unit: a retrospective study - Amira M. Sabry; Yasmeen Mansi; Halaallah Zeinelabdeen; Amir Fawzy Kamal (Egyptian Pediatric Association Gazette)
Abstract Background Congenital anomalies (CAs) are a leading cause of neonatal morbidity and mortality, particularly in low-resource settings. Data on the burden, risk factors, and outcomes of CAs in Egyptian NICUs remain scarce. This study aimed to investigate the patterns, associated risk factors, and short-term outcomes of neonates with CAs in a tertiary NICU in Egypt. Methods This retrospective observational study reviewed 100 neonates with major CAs admitted to Cairo University Pediatric Hospital NICU between February and September 2019. Clinical data were collected from medical records and supplemented by structured parental interviews. Anomalies were classified according to the EUROCAT system. Results Cardiovascular anomalies were the most common (34%), followed by anomalies of the ear, nose, and oral region (34%) and central nervous system (18%). Male infants accounted for 57% of cases, and 51% had consanguineous parents. Sepsis occurred in 75% of cases, most frequently in those with cardiovascular defects (40%). The overall mortality rate was 39%, with cardiovascular anomalies responsible for 51.3% of deaths. Consanguinity was significantly associated with cardiovascular anomalies (P < 0.05). Conclusions CAs, especially cardiovascular and CNS defects, remain a leading cause of neonatal morbidity and mortality in Egyptian NICUs. Strengthening early screening, infection control, and consanguinity counseling may significantly reduce adverse outcomes.